A terapia ocupacional no campo da gerontologia: uma contribuição para revisão de projetos de vida - Tiveron, Regina Maria (2008)
This research, developed with a qualitative approach, sought to investigate the contribution of Occupational Therapy combined with the assumptions of Gerontology for the review of life s projects in post-retirement. A brief bibliographic review was held on the following topics: Gerontology, ageing, Occupational Therapy, work, retirement and project of life. Later on, five subjects were selected (3 women and 2 men) for which the retirement, or the proximity of it, came to be experienced as a crisis. Initially, semi-structured interviews were conducted, with the purpose of collecting evidences, to focus on the occupational history of these subjects. Later on, each one of them, were followed for eight months in individual attendances of Occupational Therapy professionals whom had goals as a reflection on the retirement and experiences related to it. These attendances were recorded in a field journal. The interlocution of Occupational Therapy and Gerontology contributed to a work development in the ageing field, allowing a disruption in a fragmented action, facilitating the approach of processes and experiences that needed to be completed and integrated to allow the continuum of life. The tested field proposed by the Occupational Therapy proved to be a fertile ground for the rescue of abilities and desires as well as for discovering new talents. The chronological age was not an impeditive factor for the development of new projects of life. The elaborated projects prepared led the history mark and the profile of each subject, revealing a very unique result. The results reinforced the importance of pre-retirement that are not extremely brief and not limited to the provision of information on labor rights. Groups of Occupational Therapy are proposed as an important feature in these programs. The low return on retirement investment and not free services that offer real possibilities for the elderly insertion of socio-cultural and educational were limiting factors for the effectiveness of some elaborated projects. The shifting conceptions about stigmatizing the advancement of age proved to be vital, for the social integration, of the elderly, to become reality